CLIMATE FACTOR CONSIDERATION DURING ENERGY SAVING POTENTIAL ESTIMATION AT THE LEVEL OF INDIVIDUAL COUNTRIES AND REGIONS - N. A. Kislenko; Yu. S. Kopylova (Вестник университета, 2019)
The approach to the allocation of climate factors, that influence on gas consumption with consideration of their interdependence, nonlinearity and inertia of factors has been reviewed. In addition to the classical approach of linear consideration of the dependence on the degree-days of heating and air conditioning, an additional consideration of the factors of lighting and precipitation level has been offered. The nonlinearity of dependences has been modelled by power functions, and the inertia effect by averaging data for the previous few months. The proposed mechanism makes it possible to exclude climatic factors from the actual data of gas consumption and, as a consequence, to allocate the influence of macroeconomic factors and the energy saving factor.